A Wideband Antenna for GNSS Applications with Improved Orthogonal Dipole - Lin Daming; Wang Encheng; Wang Jie (International Journal of Antennas and Propagation)
This letter presents a wideband antenna for high-precision Global Navigation Satellite System (GNSS) applications. The antenna consists of a pair of improved orthogonal dipoles that are fed by a feed network with Composite Right/Left-Handed Transmission Lines (CRLH-TLs), a polygonal patch, and a reflector. By using improved orthogonal dipole, the beamwidth of the antenna is broadened. The CRLH-TLs is adopted in feed network to obtain outputs with stable phase difference. Experiment results indicate that the antenna has a less than 10-dB return-loss bandwidth in the range of 1.1 to 1.7 GHz, a 3-dB axial-ratio bandwidth from 1.2 to 1.6 GHz, and a larger than 6.37 dBi gain in the whole operating band. The measured results show that the proposed antenna has stable performance in the whole operating band, which means that it is a suitable antenna used for GNSS applications.